Gestão escolar e a incorporação de tecnologias nas escolas técnicas paulistas - Monteiro, Aneridis Aparecida (2011)
This academic research is connected to the Program of Master Degree in Education: Curriculum - "New Technologies in Education " area at the Catholic University of Sao Paulo - PUC-SP. On this research we attempted to reflect on the evolution of technology in modern society and the necessity for their incorporation in various sectors of society, including schools, consequently reflected on the need for businesses, organizations and schools seeking more productive management models, dynamic and incorporated to current society. To analyze the incorporation of technologies and the role of the manager in this process, the study chose as a starting point for continuing education activities aimed at managers Centro Paula Souza It was called Project Management and Technology School, which occurred in 2009 with the goal of enabling management teams school environments. This project was a partnership between PUC-SP, the Department of Education of the State of Sao Paulo, in Brazil and Microsoft, aimed to form managers - regional managers, supervisors, educational, technical and educational assistants, principals and vice-principals and coordinators for the insertion of the management and technology studies in their day by day school activities. Through research of qualitative approach, we sought to investigate if there was any change and what was with the insertion of technology at schools in which these managers act, after the managers participating in the Project Management School and Technology have completed the program. For this purpose, we attempted to reflect on professional education in Brazil since he was paternalistic character until today, in what is called technical education in the first chapter, in the second chapter reflected on the school administration and characteristics of the democratic and participatory management. In addition to present the proposed School Management and Technology and its features in the third chapter presents the methodological foundations of research, the presentation of the teaching units in which the study was conducted is in the fourth chapter. Chapter five presents the analysis and results during the search. Analyses that announced in Education Research Unit, at the present time, there are indications that the managers are providing situations for the use of ICT and that they are being inserted and implemented in the school environment, however, there is evidence that some teachers still that have not joined the technology and there is need for continuing education to employees and teachers. The survey also showed that the democratic management is perceived within the teaching units searches